2024
DOI: 10.3389/fendo.2023.1265372
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic peripheral neuropathy: pathogenetic mechanisms and treatment

Jinxi Zhu,
Ziyan Hu,
Yifan Luo
et al.

Abstract: Diabetic peripheral neuropathy (DPN) refers to the development of peripheral nerve dysfunction in patients with diabetes when other causes are excluded. Diabetic distal symmetric polyneuropathy (DSPN) is the most representative form of DPN. As one of the most common complications of diabetes, its prevalence increases with the duration of diabetes. 10-15% of newly diagnosed T2DM patients have DSPN, and the prevalence can exceed 50% in patients with diabetes for more than 10 years. Bilateral limb pain, numbness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 177 publications
0
2
0
Order By: Relevance
“…The growth of neural axons is affected by various regulatory factors and extracellular matrix in scar tissue and granulation tissue. For example, during tissue healing, cell growth factors secreted by the relevant cells, such as vascular endothelial growth factor (VEGF), transforming growth factor-1 (TGF-1), platelet-derived growth factor (PDGF), and fibroblast growth factors (FGFs) can promote cell growth and differentiation, which have a significant role in wound healing [ 58 ]. In this study, immunohistochemical analysis was performed on the subcutaneous injury site, and the fluorescence intensity of nerve fibers in the E10/70% and 20 kV 25 μL/min groups was lower than that of normal tissues at the one-week time point, indicating that the amount of nerve fiber growth promoted by the membrane in the E10/70% group and the fiber scaffolds in the 20 kV 25 μL/min group failed to reach the level of normal tissues in a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of neural axons is affected by various regulatory factors and extracellular matrix in scar tissue and granulation tissue. For example, during tissue healing, cell growth factors secreted by the relevant cells, such as vascular endothelial growth factor (VEGF), transforming growth factor-1 (TGF-1), platelet-derived growth factor (PDGF), and fibroblast growth factors (FGFs) can promote cell growth and differentiation, which have a significant role in wound healing [ 58 ]. In this study, immunohistochemical analysis was performed on the subcutaneous injury site, and the fluorescence intensity of nerve fibers in the E10/70% and 20 kV 25 μL/min groups was lower than that of normal tissues at the one-week time point, indicating that the amount of nerve fiber growth promoted by the membrane in the E10/70% group and the fiber scaffolds in the 20 kV 25 μL/min group failed to reach the level of normal tissues in a short period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic peripheral neuropathy (DPN) ( Bodman and Varacallo, 2023 ; Zhu et al., 2024 ) is a type of diabetic neuropathy that mainly affects the distal lower extremities and is often characterized by sensory loss, numbness, pain, gait disturbances, and amputation. A study on the characteristics of the gut microbiota in DPN showed that the abundance of Actinomycetes and Firmicutes is increased in DPN, whereas that of Bacteroides is decreased.…”
Section: Gut Microbiota and Dmmentioning
confidence: 99%